Pemberdayaan Taman Pendidikan Al-Quran (TPA) dalam Mengembangkan Kualitas Bacaan Quran pada Murid Sebagai Kader Guru TPA - thoriq, thoriq (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2024)
In empowering the Al-Qur`an Education Park (TPA) at the Baitul Mu'tashim mosque, Piyaman Village, Piyaman II Hamlet in particular, it has had a significant impact in developing the quality of Al-Qur'an reading to form a cadre of Al-Qur'an Education Park teachers. In this empowerment, various methods have been implemented to ensure the smooth running of this program. The impact of this empowerment is very positive, with a better improvement than before in children's ability to read the Koran. Apart from improving the quality of Al-Qur'an reading, TPA has also played a role as a center for social and educational activities in the sub-district. This creates an environment that supports the development of local communities, increases religious understanding, and promotes positive values. Thus, TPA is not just a religious educational institution, but also an agent of social change that has an impact on community life more broadly. The method used is Asset Based Communities Development (ABCD) by utilizing existing community assets or potential to develop this activity for the better. The results of this empowerment can serve as a guide for related parties to take concrete steps to strengthen the role of TPA and support similar efforts in other communities.